Effects of oil drops containing Lactobacillus salivarius WB21 on periodontal health and oral microbiota producing volatile sulfur compounds - Suzuki, Nao; Tanabe, Kazunari; Takeshita, Toru; Yoneda, Masahiro; Iwamoto, Tomoyuki; Oshiro, Sueko; Yamashita, Yoshihisa; Hirofuji, Takao (Journal of breath research, 2012)
The objective of this paper is to evaluate the effects of oil drops containing Lactobacillus salivarius WB21 on periodontal health and oral microbiota producing volatile sulfur compounds (VSCs). For this study, 42 subjects were randomly assigned to receive oil samples containing L. salivarius WB21 or a placebo for two weeks. Oral assessment and saliva collection were performed on days 1 and 15. Bacterial analysis was performed using the real-time polymerase chain reaction and terminal restriction fragment length polymorphism (T-RFLP). In both the experimental and placebo groups, the average probing depth, number of periodontal pockets, and the percentage of bleeding on probing (BOP) decreased while stimulated salivary flow increased on day 15. BOP was reduced in the experimental group compared with the placebo group (P = 0.010). In the experimental group, total bacterial numbers decreased, and the number of L. salivarius increased. The number of Prevotella intermedia, which is correlated with hydrogen sulfide concentration in mouth air, increased in the placebo group and did not change in the experimental group. T-RFLP analysis found that the peak area proportions representing Porphyromonas gingivalis, P. intermedia, Tannerella forsythensis, and Fusobacterium nucleatum decreased in the experimental group, although there was no significant change in the bacterial composition. Thus we observed oil drops containing L. salivarius WB21 improved BOP and inhibited the reproduction of total and VSC-producing periodontopathic bacteria compared with the placebo group, but also showed the limit of its efficacy in controlling VSCs producing and periodontal pathogens.